Problematika E-Procurement Untuk Akuntabilitas Dan Transparansi Pada Dinas PUPR Kabupaten Nganjuk - Onni Supriyono; Eka Askafi (Otonomi, 2022)
The current government procurement of goods/services is required to be done electronically or e-procurement. This model shift was caused by, among other things, non-transparent tender announcements, tender arrangements, violating procedures in the procurement process, intervention against the committee, specifications or requirements for procurement documents that were directed to certain parties and the committee was not focused on carrying out tasks due to dual/side assignments. . This study wants to describe the problems of e-procurement for accountability and transparency at the PUPR office of Nganjuk Regency. Where in this case the approach is qualitative and the type of research is a case study. Where with a qualitative approach is expected and obtained good and pure data as in the research location. The results of the study stated that the advantages of e-procurement at the PUPR Office of Nganjuk Regency are time efficiency because it is supported by online applications, data accuracy, reduces administrative costs and reduces operating costs. Apart from that from users, the advantages are that the people who participate in the auction become more competitive, improve customer services, and improve relationships with partners, in this case APH. The disadvantages of e-procurement at the Department of Public Works and Public Housing in Nganjuk Regency are the lack of adequate facilities and insufficient resources because there are still frequent system errors in e-procurement applications.